Decomposition of nitroimidazole ions: experiment and theory. Issue 19 (21st May 2015) - Feketeová, Linda; Postler, Johannes; Zavras, Athanasios; Scheier, Paul; Denifl, Stephan; O'Hair, Richard A. J.
<x xml:space="preserve">Abstract</x> The decomposition of nitroimidazoles involves the nitro functional group −NO2 irrespective of the initial charge state.